Silent brain infarction after minimally invasive cardiac surgery with retrograde perfusion. Issue 8 (15th July 2020) - Nishijima, Shuhei; Nakamura, Yoshitsugu; Yoshiyama, Daiki; Yasumoto, Yuto; Kuroda, Miho; Nakayama, Taisuke; Tsuruta, Ryo; Ito, Yujiro; Shikata, Fumiaki; Takeda, Tetsuji; Kato, Nobuyuki
Abstract: Background and Aim: There is no report on silent brain infarction (SBI) after minimally invasive cardiac surgery (MICS) with retrograde perfusion. Thus, the current study aimed to investigate the incidence of SBI after MICS using magnetic resonance imaging (MRI). Methods: This study included 174 patients who underwent MICS with retrograde perfusion between July 2014 and July 2018. Preoperative computed tomography (CT) angiography was routinely performed and vascular pathology was evaluated for patient selection. Postoperative MRI was performed to investigate the occurrence of SBI. Results: Out of the total 174 patients, 26 (14.9%) presented with SBI. A total of 61 SBI lesions were found in the 26 patients; of these, 34 (56%) SBI lesions were in the right hemisphere and 27 (44%) in the left hemisphere. SBIs were primarily observed in the posterior cerebral artery territory. Multivariate analysis revealed aortic stenosis to be the only risk factor of SBI. Conclusions: Retrograde perfusion via femoral cannulation may not increase the incidence of SBI in selected MICS patients based on preoperative CT findings.